2011
DOI: 10.5021/ad.2011.23.3.396
|View full text |Cite
|
Sign up to set email alerts
|

A Sporadic Case of Mal de Meleda Caused by Gene Mutation in SLURP-1 in Korea

Abstract: Mal de Meleda (MDM), also known as keratoderma palmoplantaris transgrediens, is a rare inherited form of palmoplantar keratoderma. It is characterized by erythema and hyperkeratosis of the palms and soles, extending to the dorsal aspects of the hands and feet. A 15-year-old Korean female presented with sharply demarcated hyperkeratotic plaques on the palms and soles, which extended to the dorsal surfaces of the hands and feet, in a "glove-and-socks" distribution. The histopathologic study showed marked hyperke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Some samples exhibit parakeratosis, while others show orthokeratosis [29]. There is also variation with respect to findings in the stratum granulosum, as both hypergranulosis and normogranulosis have been recorded [6,30,31]. Further, there is histologic involvement beyond the epidermis into the upper dermis with a perivascular lymphocytic dermal infiltrate [30][31][32].…”
Section: Histologymentioning
confidence: 97%
See 1 more Smart Citation
“…Some samples exhibit parakeratosis, while others show orthokeratosis [29]. There is also variation with respect to findings in the stratum granulosum, as both hypergranulosis and normogranulosis have been recorded [6,30,31]. Further, there is histologic involvement beyond the epidermis into the upper dermis with a perivascular lymphocytic dermal infiltrate [30][31][32].…”
Section: Histologymentioning
confidence: 97%
“…Subsequent to its initial description in 1826, the disease has been reported in at least 19 countries outside of Croatia including Algeria, Chile, China, Germany, India, Indonesia, Italy, Japan, Korea, Laos, Libya, The Netherlands, Pakistan, Saudi Arabia, Scotland, Sweden, Tunisia, Turkey, and the United Arab Emirates [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Historymentioning
confidence: 99%
“…Met1Lys (Emirates Bedouin [15]); Ivs1 + 1G > A (Pakistani [16]); Trp15Arg (German [15], Scottish [3], and Dutch [17]); 82delT (Tunisian [3], Scottish [3], Algerian [3], Croatian [9], Kurdish [10], and Italian [11]); Ivs2 + 1G > A (Algerian [3]); Cys43Stop (Turkish [18]); Arg71Pro (Dutch [17]); Cys77Ala (Tunisian [4]); Pro82Ser (Turkish [19]); Gly86Arg (Palestinian [15], Turkish [15]), and Pakistani [16]), Korean [20], Taiwanese [21]); Arg96Stop (Croatian [9], Turkish [10], Korean [20], and Pakistani [16]); Lys98Pro (Turkish [22]); Cys99Tyr (Tunisian [12]); and Arg71His (patient was reported in a study from France, and the origin is not reported [23]).…”
Section: Figurementioning
confidence: 99%
“…[6][7][8][9][10][11] Histologically, the lesions show hyperkeratosis and acanthosis without epidermolysis in the epidermis, accompanied by perivascular lymphocytic infiltrate in the dermis. 1,13 Cases of mal de Meleda with SLURP1 mutations have been reported in Algerian, 1 Bedouin, 14 Chinese, 15 Croatian, 1 Dutch, 16,17 German, 14,16,18 Indian, 19 Indonesian, 20 Italian, 21 Japanese, 6,22 Korean, 23 Kurdish, 2 Libyan, 24 Pakistani, 25 Palestinian, 14 Scottish, 18 Swedish, 26 Taiwanese 27,28 Tunisian, 18,21,29 and Turkish descents. 1,13 Cases of mal de Meleda with SLURP1 mutations have been reported in Algerian, 1 Bedouin, 14 Chinese, 15 Croatian, 1 Dutch, 16,17 German, 14,16,18 Indian, 19 Indonesian, 20 Italian, 21 Japanese, 6,22 Korean, 23 Kurdish, 2 Libyan, 24 Pakistani, 25 Palestinian...…”
Section: Introductionmentioning
confidence: 99%